2021
DOI: 10.1073/pnas.2011809118
|View full text |Cite
|
Sign up to set email alerts
|

Do conversations end when people want them to?

Abstract: Do conversations end when people want them to? Surprisingly, behavioral science provides no answer to this fundamental question about the most ubiquitous of all human social activities. In two studies of 932 conversations, we asked conversants to report when they had wanted a conversation to end and to estimate when their partner (who was an intimate in Study 1 and a stranger in Study 2) had wanted it to end. Results showed that conversations almost never ended when both conversants wanted them to and rarely e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Carl Rogers (1995), for example, characterized active listening as "one of the most potent forces for change that I know" (p. 116). 8 In spite of a growing body of work investigating conversations -especially around misperceptions in conversations (e.g., Boothby et al, 2018;Cooney et al, 2017;Kumar & Epley, 2020;Mastroianni et al, 2021;Zhao & Epley, 2021) and ideological disagreement (Kubin et al, 2021;Yeomans et al, 2020) -listening has been largely overlooked, and it is only recently that social psychologists have turned their attention to it (e.g., see Hart et al, 2021;Huang et al, 2017;. Listening is a channel through which people orient, relate, and connect, and is a fundamentally social psychological phenomenon.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Carl Rogers (1995), for example, characterized active listening as "one of the most potent forces for change that I know" (p. 116). 8 In spite of a growing body of work investigating conversations -especially around misperceptions in conversations (e.g., Boothby et al, 2018;Cooney et al, 2017;Kumar & Epley, 2020;Mastroianni et al, 2021;Zhao & Epley, 2021) and ideological disagreement (Kubin et al, 2021;Yeomans et al, 2020) -listening has been largely overlooked, and it is only recently that social psychologists have turned their attention to it (e.g., see Hart et al, 2021;Huang et al, 2017;. Listening is a channel through which people orient, relate, and connect, and is a fundamentally social psychological phenomenon.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Recent work has sought to examine when people choose to end natural conversations, both in the lab and in real life, and reported that the preferred time to end a conversation rarely aligns across interacting partners 72 . Although many features of the content of conversations will influence their value that go beyond the fairness manipulation deployed in this experiment, our results point to a potential computational explanation for a lack of alignment.…”
Section: Changing One's Principles Such As What One Considers As Fair Behaviour Based On What Is the Socialmentioning
confidence: 99%
“…Despite almost all conversations, and many relationships, necessarily ending at some point 17 , little is known about how people decide when to leave a social interaction. Existing research has focused on what content leads to people leaving a conversation, the phrases used to end them, or examined how misaligned people's preferences are for the duration of an interaction [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Or imagine being engaged in a fascinating conversation and the other person says, much to your chagrin, 'Well, I'd better go'. If these imagined situations feel familiar to you, you are apparently not alone: recently published research from Mastroianni, Gilbert, Cooney, and Wilson [1] provides evidence that conversations almost never end when people want. Across two studies, participants reflecting on their last in-person conversation or a conversation that had just occurred in the laboratory reported that only 15.6% of the time did the conversation end when they desired it to end (n = 1173 pre-exclusions; https://osf.io/8k4aj/).…”
mentioning
confidence: 99%